THE EFFECTIVENESS OF USING AUDIO-VISUAL MEDIA IN TEACHING WRITING TO THE SEVENTH GRADE STUDENTS AT SMP AL-IKHLAS LUBUKLINGGAU - Sefi Enjelia (LP3MKIL, 2026)
This research aims to prove whether there is significantly effective or not to use Audio-Visual Media in teaching Writing for the seventh grade students at SMP Al-Ikhlas Lubuklinggau. In this research, the researcher used pre-experimental method with one group pre-test and post-test. The population of this research was all of the seventh grade students at SMP Al-Ikhlas Lubuklinggau. Then the sample of this research was class VII B and total number of sample was 20 students. The sample of this research was taken through simple random sampling. In collecting data, the researcher used the written test that was given twice to the students, pre-test and post-test. The researcher analyzed the data through individual score and normality testing. The results showed that were 8 students passed the pre-test and 12 students failed in pre-test. While in the post-test, the students’ score increased, there were 12 students mastered the post-test and 2 students failed the post-test. In pre-test mean score was 55.25 and mean score in post-test was 73,25. The result of paired t-test, tobtained was 7.5 and ttable was 1.7291. it meant that the null hypothesis (Ho) was rejected and alternative hypothesis (Ha) was accepted. Therefore it was significantly effective to teach Writing skill by using Audi-Visual media to the seventh grade students at SMP Al-Ikhlas Lubuklinggau.